2010
DOI: 10.1111/j.1365-2036.2010.04426.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of midodrine on the natriuretic response to furosemide in cirrhotics with ascites

Abstract: SUMMARY Background Resistance to loop diuretics is common in patients with ascites. Diminished glomerular filtration rate (GFR) is thought to mediate resistance to loop diuretics. Midodrine, a commonly used alpha-1 agonist, has been shown to improve GFR in non-azotemic patients with cirrhosis. Aim To conduct a randomized, double-blind, placebo-controlled, cross-over study to test the hypothesis that midodrine significantly increases natriuretic response of IV furosemide in non-azotemic cirrhotics with ascit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In contrast to loop diuretics, data from Dao and Villeneuve suggest that for triamterene, a potassium‐sparing diuretic, despite having markedly elevated plasma levels in cirrhotics with ascites as compared with healthy volunteers, there was no difference in the magnitude of its diuretic response …”
Section: Resultsmentioning
confidence: 99%
“…In contrast to loop diuretics, data from Dao and Villeneuve suggest that for triamterene, a potassium‐sparing diuretic, despite having markedly elevated plasma levels in cirrhotics with ascites as compared with healthy volunteers, there was no difference in the magnitude of its diuretic response …”
Section: Resultsmentioning
confidence: 99%
“…28 In addition, prior studies have reported timed urine sodium output after oral furosemide administration as a valid PD end point. [20][21][22] …”
mentioning
confidence: 99%
“…Previous studies that evaluated drug disposition in bariatric surgery recipients have focused on individual compounds (eg, metformin, sertraline, tacrolimus, and cyclosporine), and they yielded conflicting results. [20][21][22][23][24] The drug-metabolizing profile of an individual can be evaluated by studying the catalytic activity of several CYP enzymes, all in one experimental session using probe substrates that are selective and specific for respective CYP enzymes. The term "pharmacokinetics" (PKs) is defined as the quantitative analysis of the processes of drug absorption, distribution, and elimination that determine the drug concentration achieved with time, whereas "pharmacodynamics" (PDs) deals with the relationship between the drug concentration and both the desired and adverse effects produced with time.…”
mentioning
confidence: 99%
“…That is, the more the systemic circulation became vasoconstricted, the better the renal hemodynamics and the greater the renal sodium excretion. However, when midodrine is given to patients with normal hemodynamics and normal renal function, there does not appear to be any additional beneficial effects on renal function or sodium excretion [69].…”
Section: Midodrinementioning
confidence: 95%